Diseño de un centro de salud sostenible con energía renovable fotovoltaica en la localidad de santa teresa en el municipio de Medina – Cundinamarca (2024)
The design of our sustainable health center powered by renewable photovoltaic energy represents an innovative approach towards more sustainable health. This project seeks not only to raise medical standards, but also to establish an eco-efficiency paradigm. The adoption of hybrid solar panels not only responds to the need for sustainable energy and reducing dependence on fossil fuels, but also ensures the continuity of health services during power outages, the design of health center that uses energy renewable photovoltaic as the main source of electricity, ensures a sustainable, technically and economically viable energy supply for the community strategically located in the town of Santa Teresa in the municipality of Medina in the department of Cundinamarca and that, with its generous solar exposure, the center health is positioned as an exemplary model of sustainability. This investment not only benefits the health of the community, but also the long-term health of our planet, ushering in a new era of healthcare and environmental responsibility.